Development of coverage and its evaluation in the treatment of chronic wounds - Marcia Diana Umebayashi Zanoti; Helena Megumi Sonobe; Sidney José Lima Ribeiro; Ana Maria Minarelli Gaspar (Universidad de Antioquia, 2017)
Objective. To describe the development of the bacterial cellulose coating with anti-inflammatory Ibuprofen (BC/ Ibu) and to evaluate the cicatrization process with its use in patients with chronic wounds of venous and diabetic etiology. Methods. Longitudinal descriptive study. The cellulose membrane, cultivated with bacteria Gluconacetobacter xylinus and with incorporation of Ibuprofen, was used in the treatment of patients with chronic wounds in public health services in a Brazilian municipality. The ideal coverage characteristics were evaluated through physical, chemical and cell proliferation tests. Results. The sample consisted of 14  patients (10 women and 4 men), 8 with venous ulcer, 5with diabetic foot and one with mixed wound. There was  reduction of area and pain in lesions; total healing of 3 wounds; and debridement of the devitalized tissue in 5 wounds with  increased area. The use of the membrane was important in the reduction of pain, exudation and ease in the accomplishment of the curative. Conclusion. BC/Ibu favored the cicatrization process of patients with chronic vasculogenic wounds.   How to cite this article: Zanoti MDU, Sonobe HM, Ribeiro SJL, Gaspar AMM. Development of coverage and its evaluation in the treatment of chronic wounds. Invest. Educ. Enferm. 2017; 35(3):330-339.